Nociception and encephalogram changes in minimally anaesthetized dogs - Leow Wei Chean
This study was designed to determine the threshold for electroencephalographic evidence of nociception in minimally anaesthetized dogs following non invasive physical manipulation. Six animals were included in this study, and noxious stimulation will be given before and after administration of tramadol, 4mg/kg at 20, 40, 60 and 80 milliamperes (mA). Baseline electroencephalogram (EEG) recording was done 10 minutes before any stimulation was performed. This is then followed by EEG recording 10 minutes for each stimulation level (20, 40 , 60 and 80 mA) before and after treatment. Ti was found that both total power and median frequencies of the EEG waves showed changes before and after tramadol was given. It was also shown that tramadol exhibited evident analgesic activities when the stimulus signals were less than 60 mA. Beyond the 60mA stimulation threshold, tramadol was found to have showed diminishing analgesic. In conclusion, dosage and type of analgesics, as well as the intensity of nociceptive signals are major determinants factors that will determine the success of an analgesia regime.